Depression and quality of life in older adults residing in a vulnerable area in San Martin de Porres - Quispe Medina, Yovana Ysabel (2021)
Objectives: The objective of the study was to determine the relationship between depression and quality of life in older adults residing in a vulnerable area in San Martin de Porres, Lima - 2021. Materials and methods: The present study had a quantitative approach, its methodological design was correlational-cross-sectional. The sample consisted of 130 participants. The data collection technique was the survey and the instruments used to measure the variables were the Geriatric Depression Scale (GDS) and the WHOQOL-OLD questionnaire. Results: Regarding the general hypothesis, it was found that there is a significant relationship between depression and quality of life and (p <0.05). According to the dimensions, no significant relationship was found between depression and quality of life in its sensory capacity dimension (p> 0.05); there is a significant relationship between depression and quality of life in its autonomy dimension (p <0.05); There is no significant relationship between depression and quality of life in its dimension, past, present and future activities (p> 0.05); if there is a significant relationship between depression and quality of life in its social participation dimension (p <0.05); if there is a significant relationship between depression and quality of life in its dimension death / agony (p <0.05); and finally, if there is a significant relationship between depression and quality of life in its intimacy dimension (p <0.05). Conclusions: Regarding the general hypothesis, a strong directly proportional significant relationship was found between the main variables.